Sex differences in the burden of type 2 diabetes and cardiovascular risk across the life course - Huebschmann, Amy G.; Huxley, Rachel R.; Kohrt, Wendy M.; Zeitler, Philip; Regensteiner, Judith G.; Reusch, Jane E. B. (Diabetologia, 2019)
By 2017 estimates, diabetes mellitus affects 425 million people globally; approximately 90–95% of these have type 2 diabetes. This narrative review highlights two domains of sex differences related to the burden of type 2 diabetes across the life span: sex differences in the prevalence and incidence of type 2 diabetes, and sex differences in the cardiovascular burden conferred by type 2 diabetes. In the presence of type 2 diabetes, the difference in the absolute rates of cardiovascular disease (CVD) between men and women lessens, albeit remaining higher in men. Large-scale observational studies suggest that type 2 diabetes confers 25–50% greater excess risk of incident CVD in women compared with men. Physiological and behavioural mechanisms that may underpin both the observed sex differences in the prevalence of type 2 diabetes and the associated cardiovascular burden are discussed in this review. Gender differences in social behavioural norms and disparities in provider-level treatment patterns are also highlighted, but not described in detail. We conclude by discussing research gaps in this area that are worthy of further investigation.